2002
DOI: 10.1037/0893-164x.16.4s.s55
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of participation in a family-focused preventive intervention for substance use.

Abstract: This study reports patterns of involvement in a family-focused preventive intervention, Schools and Families Educating (SAFE) Children, targeting early predictors of risk for delinquency and drug use among 175 African American and Latino first-grade children living in economically disadvantaged inner-city neighborhoods. Three empirically derived patterns emerged: joiners, responders, and minimal responders. Joiners were immediately responsive and enthusiastic and participated fully. Responders attended fully o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
71
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 60 publications
(73 citation statements)
references
References 54 publications
2
71
0
Order By: Relevance
“…One of the largest collaborative efforts to integrate core competencies into a prevention model emanated from a multisite evaluation of preventive interventions that aim to enhance behavioral self-regulation, parental involvement, school bonding, and social competence among children and youth (Tarter, Sambrano, & Dunn, 2002). Two programs, Schools and Families Educating Children (SAFEChildren; Gorman-Smith et al, 2002) and Coping Power (Lochman & Wells, 2002), are particularly instructive.…”
Section: Role Of Core Competencies In Adolescent Substance Use Prevenmentioning
confidence: 99%
“…One of the largest collaborative efforts to integrate core competencies into a prevention model emanated from a multisite evaluation of preventive interventions that aim to enhance behavioral self-regulation, parental involvement, school bonding, and social competence among children and youth (Tarter, Sambrano, & Dunn, 2002). Two programs, Schools and Families Educating Children (SAFEChildren; Gorman-Smith et al, 2002) and Coping Power (Lochman & Wells, 2002), are particularly instructive.…”
Section: Role Of Core Competencies In Adolescent Substance Use Prevenmentioning
confidence: 99%
“…Alternatively, parents who believe they already possess strong parenting skills may assess few benefits from participating and thus be less likely to participate (Perrino, Coatsworth, Briones, Pantin, & Szapocznik, 2001;Gorman-Smith et al, 2002). Accordingly, we examined the influence of parenting efficacy and parent self-report on two intervention-targeted parenting behaviors (monitoring and involvement in child's education) on attendance trajectories.…”
Section: Parent Perceptions Of Participation Benefits Because a Key mentioning
confidence: 99%
“…The few studies that have modeled attendance patterns used methods that do not account for unobserved heterogeneity in attendance across sessions and cannot model trajectories while also accounting for the influence of predictors on trajectories (e.g., Coatsworth, Duncan, Pantin, & Szapocznik, 2006b;Gorman-Smith et al,2002). To address these limitations and also build on the limited research examining predictors of intervention participation among MA parents, the current study used growth mixture modeling (GMM;Muthen, 2002;Nagin 2005) to simultaneously model attendance patterns and examine predictors of patterns among MA parents enrolled in Bridges to High School (Bridges), a school-based universal intervention to prevent problem behaviors and academic disengagement following the middle school transition (Gonzales et al, 2012a).…”
mentioning
confidence: 99%
“…Many participant characteristics have been investigated for their relationship to parent participation in prevention and treatment targeting children's problem behavior. Family demographic variables such as minority status, lower socio-economic status, single parent status, and larger family size have been associated with indicators of lower parent participation rates (August et al 2003;Coatsworth et al 2006;Gorman-Smith et al 2002;Kazdin et al 1995;Lavigne et al 2010;Scott et al 2010). Several studies show lower parent participation is associated with higher severity of child behavior problems (August et al 2003;Boxmeyer and Lochman 2006;Gorman-Smith et al 2002;Watt et al 2007), while one study showed that parents participate more when their child has more severe behavior problems (Dumas et al 2007).…”
Section: Introductionmentioning
confidence: 92%
“…Family demographic variables such as minority status, lower socio-economic status, single parent status, and larger family size have been associated with indicators of lower parent participation rates (August et al 2003;Coatsworth et al 2006;Gorman-Smith et al 2002;Kazdin et al 1995;Lavigne et al 2010;Scott et al 2010). Several studies show lower parent participation is associated with higher severity of child behavior problems (August et al 2003;Boxmeyer and Lochman 2006;Gorman-Smith et al 2002;Watt et al 2007), while one study showed that parents participate more when their child has more severe behavior problems (Dumas et al 2007). Parents (primarily mothers) exhibiting high stress, distress, and/or mood difficulties are at risk for poor participation (Capage et al 2001;Chronis et al 2004;Kazdin et al 1995;Werba et al 2006), and one study showed that less participation was predicted by higher levels of parents' frustration in the parent-child relationship (Bloomquist et al 2009).…”
Section: Introductionmentioning
confidence: 92%